Identification of proteins from the marine red macroalga Hypnea musciformis by proteomic analysis - Fernando Edson Pessoa do Nascimento (2014)
We currently live in a fierce competition in the research development of new biotechnology products, the marine environment can be seen as a source of functional biotechnological materials. Recent studies show that within the marine environment algae stand out as organisms with great biotechnological potential by having in its composition various bioactive molecules that have diverse and intense biological activities, among all algal groups in this study emphasize the of red algae, which the kind of study is red seaweed Hypnea musciformis (Wulfen). JV Lamouroux belongs to the order Gigartinales and Hypneaceae family, abundant on the coast of CearÃ. Biotechnological and scientific works are carried out with this species, in this sense, the main objective of this work is to identify and characterize proteins existing in this organism through a proteomics approach, is a new area in science that allows bioprospect a set of proteins in an organism by using analytical tools because under specific physiological conditions the biological functioning of the system can be reflected by the proteome analysis of the same, and thus the functional gene expression. Considering the lack of studies on proteomics in seaweed and in particular the carragenÃfita Hypnea musciformis, this paper aims to develop methods for separating proteins from protein extract of Hypnea musciformis and identify the proteins expressed by the organism. In this work we have established a methodology for separating proteins of this organism from a fractionated extract with ammonium sulfate and by mass spectrometry to identify proteins of some kelp, thus being of fundamental importance for the enrichment of macroalgae in the proteomics literature marine. The results of this work are consistent with our objective was the identification of three proteins by mass spectrometry using electrospray ionization type protein fraction of 20-40% and the identification of some proteins by Mascot